Policy innovations and sectoral credit expansion in Kenya - Samuel Tiriongo; Farida Abdul (Kenya Bankers Association (KBA), 2017)
The paper examines the bank lending channel of monetary policy specifically testing if there is any asymmetric response of sectoral credit to policy innovations on the Central Bank Rate (CBR), Cash Reserve Requirement (CRR), and Foreign Exchange (FX) transactions by CBK. Using a SVAR specification, where the requisite order of variables was guided by literature as well as practical realities in line with the conduct of monetary policy in Kenya. A seven variable SVAR was specified. The findings indicate that there are asymmetric effects of policy innovations on bank reserves when the aggregate credit to private sector is considered. CBR and FX transactions innovations do not seem to significantly impact on bank reserves, even though any changes in the bank reserves when these instruments are actively in use translate to significant changes in overall credit adjustments. But an active use of CRR leads to significant changes in bank reserves. However, when this instrument is active, the resultant change in bank reserves is not translated into credit allocation. Asymmetric effects on sectoral credit allocation when the three policy innovations are triggered was tested. This revealed that when CBR is applied, there is a significant change in bank reserves, which is also transmitted significantly to changes in credit allocation to the key sectors of the economy. And in fact, there is a stronger effect when CRR is used as an instrument of monetary policy. The use of FX transactions in this case does not seem to show significant influence on bank reserves. Even when any changes in bank reserves when FX transactions is used still leads to a significant adjustment in sectoral credit, but to a few sectors. The study therefore recommends a careful choice of monetary policy tool to use if the credit channel of monetary policy is expected to yield desirable results on credit expansion.
Keywords: 330; Geldpolitik; Geldpolitische Transmission; Bankenliquidität; Kreditgeschäft; Kenia